Carbohydrate Self‐Assembly at Surfaces: STM Imaging of Sucrose Conformation and Ordering on Cu(100). Issue 25 (24th May 2019) - Abb, Sabine; Tarrat, Nathalie; Cortés, Juan; Andriyevsky, Bohdan; Harnau, Ludger; Schön, J. Christian; Rauschenbach, Stephan; Kern, Klaus
Abstract: Saccharides are ubiquitous biomolecules, but little is known about their interaction with, and assembly at, surfaces. By combining preparative mass spectrometry with scanning tunneling microscopy, we have been able to address the conformation and self‐assembly of the disaccharide sucrose on a Cu(100) surface with subunit‐level imaging. By employing a multistage modeling approach in combination with the experimental data, we can rationalize the conformation on the surface as well as the interactions between the sucrose molecules, thereby yielding models of the observed self‐assembled patterns on the surface. Abstract : Finding the sweet spot : The combination of preparative mass spectrometry with scanning tunneling microscopy has enabled the imaging of the disaccharide sucrose on a Cu(100) surface with subunit‐level resolution. By employing a multistage modeling approach, the conformation of the disaccharide on the surface as well as the interactions between the sucrose molecules can be deduced.